An experimental investigation of dynamic ice accretion process on a wind turbine airfoil model considering various icing conditions. (April 2019) - Gao, Linyue; Liu, Yang; Hu, Hui
Highlights: Dynamic ice accretion process over a wind turbine blade model was characterized. Time evolutions of the surface temperature variation during the icing process were provided. The effects of ice types on the dynamic ice accretion process was quantitatively evaluated. The mechanism of icing process on a wind turbine blade was summarized. Abstract: In the present study, the dynamic ice accretion process over a typical wind turbine airfoil model (i.e., DU96-W-180 airfoil) was experimentally investigated under various icing conditions. The experimental study was conducted in the Icing Research Tunnel of Iowa State University (i.e., ISU-IRT). Different icing conditions (i.e., rime, mixed and glaze) that wind turbine may experience in winter were reproduced by manipulating the airflow temperature, velocity, and liquid water content (LWC) in ISU-IRT. While a high-speed imaging system was used to reveal the dynamic ice accretion process over the surface of the test model, an infrared (IR) thermal imaging system was used to map the corresponding temperature distributions over the ice accreting airfoil surface. Time variations of the ice thickness accreted along the leading edge (LE) of the test model were extracted based on the acquired high-resolution images of the ice accretion process under different test conditions. It was found that, due to the obvious runback of the impacted water (i.e., formation of water film and rivulets) over the airfoil surface, the growth rate of the ice layer accreted along the airfoil leading edge was much slower under the glaze icing condition, in comparison with those under the rime and mixed icing conditions. Such surface water transport behavior was also found to expand the ice influencing region. From the temperature evolutions during the dynamic icing processes, the transient processes of droplet impingement, water film/rivulets formation, and ice roughness growth were temporally resolved, providing comprehensive details of the unsteady heat transfer during the dynamic icing process. While the surface temperature increment due to the direct droplet impingement was found to decrease monotonously along the chord in rime case, a stream-wise 'plateau' region was observed in the glaze and mixed icing cases due to the complex multiphase mass/heat transfer associated with the surface water transport behaviors.